IMPROVING THE ABILITY TO LEARN AQIDAH AKHLAK ON SENTENCE MATERIAL THAYYIBAH ISTIGFAR IN CLASS VI B MIN 14 BANJAR - Sumarni, Sumarni (JURNAL EDUSCIENCE, 2023)
This Classroom Action Research was carried out at MIN 14 Banjar in the 2022/2023 academic year by recruiting 34 students in class VI B consisting of 17 girls and 17 boys. This research is based on the phenomenon of lack of learning outcomes in class VI B students, especially in the Kali Thayyibah istigfarsolder. Therefore, researchers are interested in making efforts to improve and improve students' learning abilities by using a habituation approach as a learning tool. There are 4 stages carried out by researchers in preparing for this study, namely planning, implementing, observing, and reflecting. By carrying out 4 meetings in two predetermined cycles, the researchers found a significant increase in learning outcomes at each meeting on a regular basis. Teacher activity increased by 33.34 from 63.33 to 96.67 at the end of cycle II, the second meeting. Student activity also increased by 20.6 from an average of 75 in the pre-observation to 9.56 at the end of cycle II, the second meeting. And student learning outcomes experienced an increase, which at the first meeting of the two cycles I, students obtained learning outcomes of 7.94. Then, at the second meeting of cycle II, student learning outcomes increased to 9.47, which means an increase of 2.68.Keywords:Aqidah Akhlah, Thayyibah, Istigfar